Social, economic and environmental implications of the COVID-19 pandemic - Maqbool, Imran; Riaz, Muhammad; Siddiqi, Umar Iqbal; Channa, Jamil Ahmed; Shams, Muhammad Shahid (Frontiers in Psychology, 2023)
The Covid-19 coronavirus pandemic led to global lockdowns that severely curtailed economic activity. It is a rare project that will shape the agenda of the study, with significant impacts. There are five sets of issues: short-term effects on oil, economic and agricultural policies, including regulations and COP26; long-term implications of monetary and fiscal intervention and investment in green agreements on future generations; prospects for further de-globalization and its effect on climate change and nature; intergenerational environmental consequences, including debt and polling.